Disclosure of conflicts of interest in the Portuguese Journal of Family Medicine during 2019 - Cossutta, Fabrizio (2023)
Introduction: Public trust in scientific research and the credibility of published scientific articles are influenced by the way authors disclose their conflicts of interest (COI). In this study we analysed how financial COI are disclosed in the Portuguese Journal of Family Medicine, comparing authors’ self-disclosure with the data gathered in the Infarmed’s sunshine platform (Plataforma de Comunicações – Transparência e Publicidade). Methods: We reviewed all articles published in the Portuguese Journal of Family Medicine between January 2019 and December 2019. Authors were categorized on concordance between self-reported disclosures and payments listed in the database. Authors who authored multiple articles were counted as new authors since each paper offered a new opportunity for COI disclosure. Results: Of the 56 articles surveyed (a total of 67, 11 excluded), none disclosed any financial COI and 48 articles (85.7%) had at least one author with non-disclosed financial COI. Of the 196 authors surveyed (a total of 207, 10 were excluded for not being doctors, and one for risk of ambiguous identification due to homonymy), 112 (57.1%) had undisclosed payments. Undisclosed payments totalled over € 127,025.37. Discussion: No author declared the existence of financial COI, possibly because they did not consider the relationship between the payments received and the purpose of the study itself to be relevant. The omission of COI must be considered bad practice and therefore transparency measures in the scientific dissemination process need to be strengthened.